1981
DOI: 10.1677/joe.0.0890205
|View full text |Cite
|
Sign up to set email alerts
|

Delay of the Selective Surge of Follicle-Stimulating Hormone by Bovine Follicular Fluid During the Period of Ovulation Induced by Human Chorionic Gonadotrophin in Dioestrous Rats

Abstract: When bovine follicular fluid (BFF) was given i.p. three times at intervals of 3 h from 17.00 to 23.00 h to dioestrous rats pretreated with 10 i.u. human chorionic gonadotrophin (HCG) at 17.00 h on the day of dioestrus (day 0), the selective surge of FSH at 02.00 h on day 1 was suppressed in a dose-dependent manner. Three i.p. injections of 0.5 ml BFF completely suppressed the FSH rise in plasma at 02.00 h on day 1, but the time of premature ovulation induced by HCG was not altered. In these animals treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

1982
1982
1998
1998

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
1
5
1
Order By: Relevance
“…This observation is not consistent with previous reports in cyclic rats, in which it was suggested that the periovulatory FSH surge in 4-or 5-day cyclic rats is responsible for follicular re¬ cruitment for the next oestrous cycle (Schwartz, 1974;Welschen & Dullaart, 1976;Sasamoto et al 1977: Hirshfield & Midgley, 1978aHoak & Schwartz, 1980;Hirshfield & DePaolo, 1981;Sasamoto et al 1981;Mizuno et al 1983). However, the development and maturation of Graafian follicles were observed during late pregnancy and lactation without an FSH surge (Richards & Kersey, 1979;Richards, 1980;Taya & Sasamoto, 1981).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This observation is not consistent with previous reports in cyclic rats, in which it was suggested that the periovulatory FSH surge in 4-or 5-day cyclic rats is responsible for follicular re¬ cruitment for the next oestrous cycle (Schwartz, 1974;Welschen & Dullaart, 1976;Sasamoto et al 1977: Hirshfield & Midgley, 1978aHoak & Schwartz, 1980;Hirshfield & DePaolo, 1981;Sasamoto et al 1981;Mizuno et al 1983). However, the development and maturation of Graafian follicles were observed during late pregnancy and lactation without an FSH surge (Richards & Kersey, 1979;Richards, 1980;Taya & Sasamoto, 1981).…”
Section: Discussioncontrasting
confidence: 99%
“…It is postulated that the prolonged surge of folliclestimulating hormone (FSH) during the periovulatory period plays a major role in the recruitment of fol¬ licles for the next oestrous cycle in the normal cyclic rat (Schwartz, 1974;Welschen & Dullaart, 1976;Sasamoto, Harada & Taya, 1977Hirshfield & Midgley, 1979aJr, Hoak & Schwartz, 1980Sasamoto, Otani & Shirota, 1981). It has recently been suggested that the secondary surge of FSH is responsible for this selection process (Hirshfield & DePaolo, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…Other observations made in this study showed that material present in bFF, but not in rGCCM, suppressed LH secretion (see also Sasamoto, Otani & Shirota, 1981 ). An explanation has not yet been found, but this phenomenon could be a result either of varying sensitivity of the female rat pituitary cells used in the present study, due to cyclic changes in hormonal priming in vivo, or of the presence of other substances, which affect gonadotrophin secretion, in follicular fluid (de Jong et al 1979).…”
Section: Discussionsupporting
confidence: 75%
“…The selective release of FSH is inhibited by the injection of charcoal stripped bovine follicular fluid [29], and plasma levels of inhibin decrease as does the selective release of FSH, after 10 IU hCG treatment in diestrous rats [9]. These data indicate that the selective release of FSH during the period of induction of ovulation is brought about by a Table 2.…”
Section: Discussionmentioning
confidence: 81%